Personality in Chronic Headache: A Systematic Review with Meta-Analysis - Sara Bottiroli; Alessia Renzi; Elena Ballante; Roberto De Icco; Grazia Sances; Annalisa Tanzilli; Tomaso Vecchi; Cristina Tassorelli; Federica Galli (Pain Research and Management)
Background. Chronic headache (CH) is a condition that includes different subtypes of headaches and that can impair different life domains. Personality traits can play a relevant role both in the development and in coping with this medical condition. The first aim of the present study is to realize a systematic review of the personality traits associated with CH compared to healthy controls; the second objective is to carry out a quantitative meta-analysis with the studies using the same instrument to assess personality traits. Method. The literature search encompassed articles published from 1988 until December 2022 on the major databases in the field of health and social sciences: PubMed, Scopus, PsychInfo, and Web of Science. Results. Thirteen studies were included in the systematic review, but only three studies were deeply explored in a meta-analysis since the only ones used a common instrument for personality assessment (Minnesota Multiphasic Personality Inventory). According to the meta-analysis, different subtypes of CH patients scored higher than healthy controls on Hypochondriasis and Hysteria Scales. The systematic review showed higher levels of depressive and anxious personality dimensions and pain catastrophizing in CH compared to healthy controls. Moreover, frequent-chronic forms and medication-overuse headache were the most symptomatic and frail categories showing higher levels of dysfunctional personality traits and psychopathological symptoms. Conclusions. These results seem to confirm a “neurotic profile” in patients suffering from CH. The identification of the main personality traits involved in the onset and maintenance of headache disorders represents an important objective for developing psychological interventions.